Gradual transitions in morphology of diamond films grown by using N-2 admixtures of CH4+H-2 gas in a hot filament assisted chemical vapour deposition system - Kshirsagar, S. T.; Kshirsagar, R. B.; Patil, P. S.; Kulkarni, A.; Mandate, A. B.; Gaikwad, A. B.; Gokhale, Suresh P. (Diamond and Related Materials, 2005)
A study of the evolution of morphology of diamond films grown as a function of N-2 gas additions to the CH4+H-2 precursor in an HF-CVD system is presented. With the increase of admixture of N2 fraction, in contrast to earlier studies, the morphology was observed first to gradually change from {111}-faceted crystallites texture to that of an intermediate cubo-octahedral crystallite texture and then gradually but finally to transform completely into that of {100}-faceted crystallites. The threshold nitrogen concentration, [N-2](thr), required to bring about the said transition in morphology was much larger than it was reported previously. Moreover, the morphology transition required a larger [N-2](thr) when a large fraction of methane was employed. Further additions of nitrogen, that just exceeded the [N-2](thr), resulted in growth of films containing slightly bigger {100}-multi-layered grains or isolated planar {100}-platelets. For extremely large nitrogen additions, the growth of nanocrystalline or amorphous carbon films was observed. The N-2 additions more than 50 vol.% did not yield any deposition. Raman scattering and photoluminescence measurements were used respectively for characterizing the quality and nitrogen doping in the films. These results are attributed to the possible catalytic role of atomic nitrogen at the growing surface. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: diamond film; hot filament CVD; morphology transitions; nitrogen

Influence of process pressure on HW-CVD deposited a-Si : H films - Jadkar, Sandesh R.; Sali, J. V.; Kshirsagar, S. T.; Takwale, M. G. (Solar Energy Materials and Solar Cells, 2005)
Hydrogenated amorphous silicon (a-Si:H) films were deposited using pure silane (SiH4) without hydrogen dilution by hot wire chemical vapor deposition (HW-CVD) technique. The electrical, optical, and structural properties of these films are systematically studied as a function of process pressure (P-r). The device quality a-Si:H films with a photosensitivity > 10(5) were deposited at a deposition rate >40 Angstrom/s at low process pressure. However, a-Si:H films deposited at higher process pressures show degradation in their electrical and structural properties. The FTIR spectroscopic analysis showed that a-Si:H films deposited at low process pressure contain hydrogen mainly in mono-hydrogen (Si-H) configuration whereas films deposited at higher process pressure have hydrogen in di-hydrogen (Si-H-2) or poly hydrogen (SiH2)(n) complexes. The hydrogen content (C-H) in the films was found to be less than 4 at.% over the entire range of process pressure studied. This indicates that the growth of a-Si:H films is mainly from the atomic species (Si and H) evaporated from the hot filament and hydrogen gets incorporated in the film via gas-phase reactions and substrate gas interactions. The band gap, however was found similar to1.71 eV or much higher. We attribute high band gap at low hydrogen content may be due to presence of microvoids. Raman spectroscopic analysis showed increase in structural disorder and Rayleigh scattering with increase in the process pressure. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Electrical properties; FTIR spectroscopy; hot wire chemical vapor deposition; hydrogenated amorphous silicon; Raman spectroscopy